Business Media in Entrepreneurship - Aulya, A N; Sutisnawati, Y (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The development of technology using the internet is increasingly inevitable. The influence of the internet makes all activities in various fields of life all online, including the existence of a web-based that can be accessed by all users with an internet-connected network that requires a browser to run it. With the internet, everything you want to find can be obtained easily, including entrepreneurs who in developing their business can use web-based as a business media. The purpose of this research is to find out the influence of web-based as an information media and also promotion for entrepreneurs, which have a role in business development to maximize the potential of the business being carried out and can also reach a broad target market. The method used in the research is a literature study. Seeing the development of technology that is increasing and also the internet which has a big influence, entrepreneurs use the internet with the help of web-based business activities by providing information and promotions on the web. With the web-based, entrepreneurs are easier to promote and provide information to customers. It is easily applied to all entrepreneurs or businesses.